Fertility protection: complications of surgery and results of removal and transplantation of ovarian tissue - Beckmann, Matthias Wilhelm; Sütterlin, Marc; Germeyer, Ariane (Reproductive biomedicine online, 2018)
Fertility-preserving measures are becoming important for patients receiving oncological treatment. One method involves cryopreservation of ovarian tissue and transplanting it when treatment is completed. We report complications resulting from surgical and fertility medicine, and the results of procedures for the removal and transplantation of ovarian tissue carried out within the FertiProtekt network. A survey using a structured questionnaire was conducted among the FertiProtekt network centres between November 2015 and June 2016. The analysis included surgical techniques used to remove and transplant ovarian tissue, surgical complications and results. Laparoscopic removal and transplantation of ovarian tissue have a low risk of complications. Surgical complications occurred in three of the network's 1373 ovarian tissue removals (n = 1302) and transplantations (n = 71); two complications (0.2%) occurred during removal and one during transplantation. Menstruation resumed in 47 out of 58 women (81%) who underwent ovarian tissue transplantation. Hormonal activity occurred in 63.2% of transplantations with a follow-up of 6 months or over. Sixteen pregnancies occurred in 14 patients, with nine births. The risks and complications of removal and transplantation of ovarian tissue are similar to those of standard laparoscopy. These procedures are becoming standard for fertility protection in cancer patients.